2023
DOI: 10.3390/ijerph20043752
|View full text |Cite
|
Sign up to set email alerts
|

Association between Glutathione S-Transferases Gene Variants and COVID-19 Severity in Previously Vaccinated and Unvaccinated Polish Patients with Confirmed SARS-CoV-2 Infection

Abstract: As the outcome of COVID-19 is associated with oxidative stress, it is highly probable that polymorphisms of genes related to oxidative stress were associated with susceptibility and severity of COVID-19. The aim of the study was to assess the association of glutathione S-transferases (GSTs) gene polymorphisms with COVID-19 severity in previously vaccinated and unvaccinated Polish patients with confirmed SARS-CoV-2 infection. A total of 92 not vaccinated and 84 vaccinated patients hospitalized due to COVID-19 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…A recent Polish study conducted by Orlewska K. et al reported that GSTP1 Ile/Val genotype was associated with higher risk of developing a severe form of the disease. However, they found that GSTM1 null and GSTT1 null genotypes had no significant association with risk of developing severe forms of COVID-19, which is in agreement with results of our study [47].…”
Section: Discussionsupporting
confidence: 92%
“…A recent Polish study conducted by Orlewska K. et al reported that GSTP1 Ile/Val genotype was associated with higher risk of developing a severe form of the disease. However, they found that GSTM1 null and GSTT1 null genotypes had no significant association with risk of developing severe forms of COVID-19, which is in agreement with results of our study [47].…”
Section: Discussionsupporting
confidence: 92%
“…Variants in GSTT1 and GSTM1 can affect PO detoxification, with null genotypes potentially increasing susceptibility to its toxic effects. GSTT1-/-genotype showed higher mortality in COVID-19 patients [15] while GSTP1 Ile/Val genotype was found to be associated with a higher risk of developing a severe form of COVID-19 in the population of vaccinated patients [16]. In our subsequent studies [17], we observed some notable differences between the MEBO and average populations, but the incidence of COVID-19 was significantly lower in the MEBO group compared to the average population.…”
Section: Discussionmentioning
confidence: 99%
“…Cytokine storm, endothelial dysfunction, oxidative stress, and cell death are the processes respon-sible for COVID-19 pathogenesis and organ damage in the severe form of the disease, including ocular lesions [25,26].…”
Section: Discussionmentioning
confidence: 99%